2020
DOI: 10.1007/s00535-020-01714-7
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcomes of patients with immunoglobulin G4-related sclerosing cholangitis: the Mayo Clinic experience

Abstract: Background The long-term outcomes of immunoglobulin G4-related sclerosing cholangitis (IgG4-SC) are not well known. Methods The outcomes of patients with IgG4-SC at Mayo Clinic (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) were compared to an age-and gendermatched (1:1 ratio) group of patients with primary sclerosing cholangitis (PSC). Results We identified 89 patients with IgG4-SC; median age at diagnosis was 67 years, 81% were males, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
2
11
0
2
Order By: Relevance
“…This result agrees with the previous study of AIP by Shiokawa et al 4 In particular, a previous studies have reported the diagnosis of bile duct cancer concurrently with the diagnosis of IgG4‐SC 5,16 . Cases of bile duct cancer diagnosed 4 months and 1.5 years after IgG4‐SC diagnosis reported 8,16 . In the present study, three cases were diagnosed with bile duct cancer.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result agrees with the previous study of AIP by Shiokawa et al 4 In particular, a previous studies have reported the diagnosis of bile duct cancer concurrently with the diagnosis of IgG4‐SC 5,16 . Cases of bile duct cancer diagnosed 4 months and 1.5 years after IgG4‐SC diagnosis reported 8,16 . In the present study, three cases were diagnosed with bile duct cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Of the 121 IgG4-SC patients, 108 (89.3%) had AIP. In previous reports, 87%-89% of IgG4-SC cases coexisted with AIP, 8,16 similar to the present study. Although there may be a possibility of confounding factors, the SIR was higher in IgG4-SC without AIP was higher than IgG4-SC with AIP in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the long term, PSC patients are at a significantly greater risk of cirrhosis and cholangiocarcinoma than are patients with IgG4-related SC [11].…”
Section: Introductionmentioning
confidence: 99%